Bioreactor Platform for Biomimetic Culture and in situ Monitoring of the Mechanical Response of in vitro Engineered Models of Cardiac Tissue - Massai, Diana; Pisani, Giuseppe; Isu, Giuseppe; Rodriguez Ruiz, Andres; Cerino, Giulia; Galluzzi, Renato; Pisanu, Alessia; Tonoli, Andrea; Bignardi, Cristina; Audenino, Alberto L.; Marsano, Anna; Morbiducci, Umberto (Frontiers in Bioengineering and Biotechnology, 2020)
In the past two decades, relevant advances have been made in the generation of engineered cardiac constructs to be used as functional in vitro models for cardiac research or drug testing, and with the ultimate but still challenging goal of repairing the damaged myocardium. To support cardiac tissue generation and maturation in vitro, the application of biomimetic physical stimuli within dedicated bioreactors is crucial. In particular, cardiac-like mechanical stimulation has been demonstrated to promote development and maturation of cardiac tissue models. Here, we developed an automated bioreactor platform for tunable cyclic stretch and in situ monitoring of the mechanical response of in vitro engineered cardiac tissues. To demonstrate the bioreactor platform performance and to investigate the effects of cyclic stretch on construct maturation and contractility, we developed 3D annular cardiac tissue models based on neonatal rat cardiac cells embedded in fibrin hydrogel. The constructs were statically pre-cultured for 5 days, and then exposed to 4 days of uniaxial cyclic stretch (sinusoidal waveform, 10% strain, 1 Hz) within the bioreactor. Explanatory biological tests showed that cyclic stretch promoted cardiomyocyte alignment, maintenance and maturation, with enhanced expression of typical mature cardiac markers compared to static controls. Moreover, in situ monitoring showed increasing passive force of the constructs along the dynamic culture. Finally, only the stretched constructs were responsive to external electrical pacing with synchronous and regular contractile activity, further confirming that cyclic stretching was instrumental for their functional maturation. This study shows that the proposed bioreactor platform is a reliable device for cyclic stretch culture and in situ monitoring of the passive mechanical response of the cultured constructs. The innovative feature of acquiring passive force measurements in situ and along the culture allows monitoring the construct maturation trend without interrupting the culture, making the proposed device a powerful tool for in vitro investigation and ultimately production of functional engineered cardiac constructs.